Accounting for war burials in the German Democratic Republic; the politics of knowledge production in the aftermath of mass death - Laura Tradii (Human Remains and Violence, 2024)
The area of Germany which became the Soviet Occupation Zone/German Democratic Republic (GDR) bore the brunt of the Soviet offensive of 1945. This last phase of the Second World War on German soil produced a sensational death toll. Yet, a systematic registration of war burials on GDR soil did not take place until the 1970s. This article analyses a particular facet of knowledge production and mass death by turning to the process of accounting for Second World War burials through lists and statistics in the socialist GDR, with a particular focus on key policy changes in the 1970s. Unpacking the reasons which prompted a large-scale registration of war burials some twenty-five years after the end of the war, I argue that the process of accounting for war deaths was shaped by both domestic and foreign politics, and in particular by evolving relations with non-socialist countries. I also demonstrate that international requirements for the visibility and accountability of war burials, as enshrined in the Geneva Conventions, generated tensions with a domestic ‘politics of history’ which required the invisibility of particular categories of dead.